Ekspansi Produk Bolu Amanda: Studi Strategi dan Potensi Pasar - Anis Fadhillah Setya Handayani; Arini Eka Saputri; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Product expansion is a strategic step often taken by companies to expand market coverage and improve competitiveness. In the culinary industry, product innovation and diversification are key to attracting the attention of consumers who are increasingly dynamic in their preferences. Bolu Amanda, as one of the cake brands that has established its position in the Indonesian market, is a clear example of how local brands can compete through product quality and effective business strategies. With an established reputation, product expansion is a logical step to respond to the growing market needs. However, product expansion is not just about adding new variants, but also about understanding market potential and consumer needs. The right strategy involves in-depth research into consumer preferences, market trends, as well as relevant innovations. In the context of Bolu Amanda, this expansion step is interesting to study, considering that competition in the food industry is getting tougher with many new players offering similar products. This requires Bolu Amanda to continue to prioritize its competitive advantages in terms of taste, quality, and branding. This article aims to explore Bolu Amanda's product expansion strategy and analyze the potential market that the brand can reach. Using a case study approach, this article will discuss how Bolu Amanda capitalizes on existing opportunities, challenges faced, and innovative steps taken to remain relevant amidst changing consumer preferences. This study is expected to provide insights not only for Bolu Amanda, but also for other industry players who want to learn successful strategies in product expansion.